The ethics of human life extension: the second argument from evolution - Gyngell, C (Oxford University Press, 2015)
One argument that is sometimes made against pursuing radical forms of human life extension is that such interventions will make the species less evolvable, which would be morally undesirable. In this paper I discuss the empirical and evaluative claims of this argument. I argue that radical increases in life expectancy could, in principle, reduce the evolutionary potential of human populations through both biological and cultural mechanisms. I further argue that if life extension did reduce the evolvability of the species this will be undesirable for three reasons: (1) it may increase the species’ susceptibility to extinction risks, (2) it may adversely affect institutions and practises that promote well-being, and (3) it may impede moral progress.